Moderate increase of serum uric acid within a normal range is associated with improved cognitive function in a non-normotensive population: A nationally representative cohort study - Wang, Jinqi; Jin, Rui; Wu, Zhiyuan; Liu, Yueruijing; Jin, Xiaohan; Han, Ze; Liu, Yue; Xu, Zongkai; Guo, Xiuhua; Tao, Lixin (Frontiers in Aging Neuroscience, 2022)
Background Associations between serum uric acid (SUA) and changes in cognitive function are understudied in non-normotensive populations and many previous studies have only considered the baseline SUA at a single time point. We aimed to examine the effects of baseline SUA and 4-year changes in SUA on cognitive changes in non-normotensive population. Methods In the China Health and Retirement Longitudinal Study (CHARLS), cognitive function was measured based on executive function and episodic memory in four visits (years: 2011, 2013, 2015 and 2018). We identified two study cohorts from CHARLS. The first cohort included 3905 non-normotensive participants. Group-based single-trajectory and multi-trajectory models were applied to identify 7-year cognitive trajectories. Adjusted ordinal logistics models were performed to assess the association between baseline SUA and 7-year cognitive trajectories, and subgroup analyses were conducted according to the presence of hyperuricemia or SUA levels. The second cohort included 2077 eligible participants. Multiple linear regression was used to explore the effect of 4-year change in SUA on cognitive change during the subsequent 3-year follow-up. Results Four distinct single-trajectories of global cognitive performance and four multi-trajectories of executive function and episodic memory were identified. Higher baseline SUA levels were significantly associated with more favorable cognitive single-trajectories (ORQ4 vs Q1: 0.755; 95% CI: 0.643, 0.900) and multi-trajectories (ORQ4 vs Q1: 0.784; 95% CI: 0.659, 0.933). Subgroup analyses revealed that the protective effect of SUA was significant in non-hyperuricemia groups or Low-level SUA groups. Additionally, changes in SUA could influence future cognitive changes. Compared with non-hyperuricemia participants with elevated SUA, non-hyperuricemia participants with decreased SUA and patients with persistent hyperuricemia had a higher risk for cognitive decline. Furthermore, only the Q3 group of changes in SUA could enhance global cognitive function compared with the Q1 group (β: 0.449; 95% CI: 0.073, 0.826). Conclusions Our study indicates that maintenance of normal SUA levels and moderate increase of SUA was advantageous in improving cognitive function or trajectories in non-normotensive population. Conversely, SUA may impair cognitive function in patients with persistent hyperuricemia.